UPAYA UNOCHA DALAM PENYELESAIAN KRISIS KEMANUSIAAN DI SUDAN SELATAN TAHUN 2013-2017 - Yulianti Puspita Dewi; Sri Yuniati; Fuad Albayumi (Journal of Social and Political Science)
South Sudan became a separate country from Sudan in 2011. Soon after its independence, conflict broke out between the government and rebel forces in South Sudan in 2013. The concentration of attacks which often happended in the civilians’ production fields and houses area resulted in hyperinflation of food prices and civilian casualties. Food shortages and the threat of violence are felt by civilians in South Sudan, causing a humanitarian crisis that threatens the survival of civilians. The government which is supposed to protect civilians is indeed more focused on defeating rebel forces and was worsening the crisis due to prolonged conflict. The conditions of the widespread crisis and the suffering felt by civilians in South Sudan forced them to seek refuge in the bases of the United Nations and other countries around South Sudan. This article discusses the UNOCHA's efforts in resolving the humanitarian crisis in South Sudan in 2013-2017. This study used qualitative method by using secondary data obtained from books, print media, articles, journals, online news media to the official website of the relevant organizations which were then analyzed and explained descriptivelyqualitatively. The results of this study showed that as the representatives of the international community, UNOCHA had a responsibility to protect civilians in South Sudan by making various efforts, including making policy agendas, coordinating, providing information, conducting advocacy, and allocating humanitarian funding to resolve the humanitarian crisis in South Sudan. Keywords: humanitarian crisis, responsibility to protect, UNOCHA